Effect of used rice straw of mushroom cultivation on growth performance and plasma metabolites in beef cattle (Bangladesh Journal of Animal Science, 2017)
The present experiment was designed to know the feasibility of using rice straw used as bedding materials for mushroom cultivation as cattle feed and its effect on the growth performance and plasma metabolites in ten beef cattle (BW 73±7 kg; 1 year). The animals were divided into two groups and fed two diets using a crossover design for a period of 60 days each. Diet one was control diet (CL-diet) composed of rice straw, dhal grass, wheat bran, and mustard oil cake and in another diet 10% of rice straw of CL-diet was replaced by the rice straw used as bedding material for mushroom cultivation, which was considered as mushroom straw diet (URS-diet). In both the dietary treatments the animals were fed at 1.5 times of maintenance energy and protein requirement. The animals were weighed once a week throughout the experimental period, and the blood samples were collected on the day 60 of each experiment. The acid detergent fiber was slightly lower and neutral detergent fiber was slightly higher (P < 0.05) for URS-diet compared to CL-diet. The crude protein and crude ash contents were higher (P < 0.05) in URS-diet compared to CL-diet. Body weight gain was greater for URS-diet compared to CL-diet. Plasma concentration of glucose, and blood urea were comparable between dietary treatments. Plasma total cholesterol, triglyceride, HDL-C, and LDL-C were lower in URS-diet compared to CL-diet. It could be concluded that, the URS-diet could be fed to cattle without any adverse effect on growth and plasma lipid profile.Bang. J. Anim. Sci. 2016. 45 (3): 40-45